2010
DOI: 10.1111/j.1398-9995.2010.02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics reduce allergen-induced T-helper 2 response and improve peak expiratory flow in allergic asthmatics

Abstract: Four-week treatment with synbiotics had no effect on bronchial inflammation and LAR, but did significantly reduce systemic production of Th2-cytokines after allergen challenge and improved PEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 40 publications
(40 reference statements)
2
57
0
4
Order By: Relevance
“…Although a slightly different ratio of oligosaccharides was used in previous studies (9:1:2), these findings extend earlier observations that a specific prebiotic mixture decreases lower airway hyperreactivity, IgE serum levels, and lung inflammatory cell influx in an ovalbumin-induced murine asthma model (57). Furthermore, it has been reported that administration of scGOS/lcFOS in combination with Bifidobacterium breve M-16V for a period of 4 weeks significantly reduced systemic production of Th2 cytokines after allergen challenge in patients with asthma and house dust mite allergy (53). These studies all underscore the immune-modulating and, more specifically, Th1-supporting effect of these specific oligosaccharide mixtures.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although a slightly different ratio of oligosaccharides was used in previous studies (9:1:2), these findings extend earlier observations that a specific prebiotic mixture decreases lower airway hyperreactivity, IgE serum levels, and lung inflammatory cell influx in an ovalbumin-induced murine asthma model (57). Furthermore, it has been reported that administration of scGOS/lcFOS in combination with Bifidobacterium breve M-16V for a period of 4 weeks significantly reduced systemic production of Th2 cytokines after allergen challenge in patients with asthma and house dust mite allergy (53). These studies all underscore the immune-modulating and, more specifically, Th1-supporting effect of these specific oligosaccharide mixtures.…”
Section: Discussionsupporting
confidence: 77%
“…Some nondigestible oligosaccharides are called prebiotics, because they stimulate the growth of commensal bacteria known to be beneficial to the host (38). It has been shown that infant formula including specific nondigestible carbohydrates, like shortchain galactooligosacharides (scGOS) and long-chain fructooligosaccharides (lcFOS), affects the incidence of upper respiratory tract infections and severity of asthma and lowers IgE antibody titers in atopic disease (1,53,54). In addition, in infants receiving scGOS, lcFOS, and pectin-derived oligosaccharides (pAOS), a preventive effect was found for development of atopic dermatitis (17).…”
Section: R Espiratory Syncytial Virus (Rsv) a Pneumovirus In The Familymentioning
confidence: 99%
“…En una publicación reciente de Van de Pol y col (2010), se demostró que un simbiótico, mezcla de la cepa Bifidobacterium breve M-16V con varios prebióti-cos, reduce significativamente la producción de citocinas Th2 y mejora el pico espiratorio forzado (PEF) después del reto alergénico en adultos asmáticos y alérgicos a los ácaros (42). Otros estudios mostraron que el consumo de diferentes cepas de probióticos mejora los síntomas de la enfermedad alérgica en personas con riesgo de dermatitis atópica (43)(44)(45)(46)(47).…”
Section: Alergiasunclassified
“…87 Also, synbiotics (90% short-chain galacto-oligosaccharides, 10% long-chain fructo-oligosaccharides: Immunofortis and Bifidobacteriu breve M-16V) had no effect on bronchial inflammation and the late asthmatic response but did significantly reduce systemic production of Th2-cytokines after allergen challenge and improved peak expiratory flow for patients with asthma and HDM allergy. 88 The other randomized, double-blind, placebo-controlled, allergy-prevention trial used a combination of LGG, L. rhamnosus LC705, B. breve Bb99 and Propionibacterium freudenreichii ssp. Shermanii prenatally and during the 6 months after birth.…”
Section: Combination Effect Animal Modelmentioning
confidence: 99%